Formalized Hrm Structures: Coordinating Equal Employment Opportunity Or Concealing Organizational Practices? - Konrad, Alison M.; Linnehan, Frank (Academy of Management Journal, 1995)
Do formalized human resources management (HRM) structures promote goals of equal employment opportunity and affirmative action or symbolize good faith in the absence of real change? We examined the antecedents and outcomes of formalized HRM structures in over a hundred organizations, assessing the presence of ?identity-conscious? and ?identity-blind? HRM structures. Findings indicated that identity-conscious structures were associated with some positive indicators of the employment status of women and people of color. II was concluded that such practices, although perhaps adopted for symbolic purposes, improved the employment status of protected groups.